Laboratory study of proppant on shale fracture permeability and compressibility. (15th June 2018) - Tan, Yuling; Pan, Zhejun; Liu, Jishan; Feng, Xia-Ting; Connell, Luke D.
Highlights: Fracture permeability is closely related to proppant packing and layer number. Fracture compressibility decreases for propped fracture. Adding proppant decreases the anisotropy ratio of permeability of the fracture. Abstract: Hydraulic fracturing is key for shale gas production and fracture permeability or conductivity is one of the most important parameters for gas production rate. Investigating the proppant distribution and fracture permeability in the field is difficult, therefore, laboratory study is a good alternative. In this work, the effect of the layer number and type of proppant on fracture permeability and compressibility were investigated. A cubic shale sample from the Cambrian Niutitang Formation at Sangzhi, Hunan Province, China, was used in this work. Sands and glass beads of different number of layers were added into an artificial fracture and seven cases, including original sample, non-propped fracture, and four kinds of propped fractures were considered. Permeability at three gas pressure steps and five confining pressure steps were measured in each case at two flow directions. Microscopic X-ray computed tomography was used to detect the distributions of proppant, and the relationship with permeability and its anisotropy was studied. A permeability model combining the stress and Klinkenberg effects was used to match experimental data and a new fracture compressibility model was proposed to predict the change of fracture compressibility with the layer number of proppant. It was found that permeability and compressibility of proppant supported fracture are closely related to proppant packing pattern and layer number, as well as the permeability anisotropy. These results improve our understanding on permeability behaviour for the proppant supported fracture and can assist in the model of fracture permeability and simulation of shale gas production.